Pengaruh Penggunaan Agregat Kasar dan Halus dari Quarry Siulak Deras dan Quarry Sungai Rumpun di Kabupaten Kerinci terhadap Kuat Tekan Beton Normal - Syafri Wardi; Dandia Dinul Rahmi (Yayasan Literasi Sains Indonesia, 2022)
In Kerinci Regency, especially around areas of Gunung Tujuh and Siulak areas, people generally use materials from Sungai Rumpun quarry and Siulak Deras quarry for the concrete mixture. A preliminary test by organic impurity test showed that the organic substances in the aggregate from the Sungai Rumpun quarry had a high organic content, while the aggregate from the Siulak Deras quarry had a low organic content. Therefore, this study aims to investigate the characteristics of the aggregate from Sungai Rumpun quarry and the Siulak Deras quarry and to determine the effect of the use of coarse and fine aggregate from both quarries on the compressive strength of concrete. This study is an experimental research that is conducted at the Civil Engineering Laboratory of the Padang Institute of Technology (ITP). In this study, the tests for physical properties of coarse and fine aggregates are conducted, then samples for the concrete compressive test are prepared, and the compressive strength test is carried out. Based on the results of this study, it can be concluded that aggregates from the Sungai Rumpun quarry are not recommended to be used for the concrete mixture of normal strength concrete (fc'=20 MPa), because the results of the compressive strength test showed that the average compressive strength does not reach the designed compressive strength (fc'). On the other hand, the aggregates from the Siulak Deras are recommended to be used for the concrete mixture of normal strength concrete because the compressive strength reaches the designed compressive strength.